2018
DOI: 10.1371/journal.ppat.1007475
|View full text |Cite
|
Sign up to set email alerts
|

Gluconeogenesis using glycerol as a substrate in bloodstream-form Trypanosoma brucei

Abstract: Bloodstream form African trypanosomes are thought to rely exclusively upon glycolysis, using glucose as a substrate, for ATP production. Indeed, the pathway has long been considered a potential therapeutic target to tackle the devastating and neglected tropical diseases caused by these parasites. However, plasma membrane glucose and glycerol transporters are both expressed by trypanosomes and these parasites can infiltrate tissues that contain glycerol. Here, we show that bloodstream form trypanosomes can use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 64 publications
3
39
0
Order By: Relevance
“…While glycerol could be converted into glucose, it is unlikely to account for the rescue as the energy required for gluconeogenesis exceeds that generated from glycolysis. Instead, it is possible that Leishmania parasites metabolize glycerol into glycerol-3-phosphate (by glycerol kinase) and then dihydroxyacetone phosphate (by the mitochondrial FAD-dependent glycerol-3-phosphate dehydrogenase) which can be incorporated into the glycolysis pathway, as described in T. brucei [50,51]. We also observed increased uptake of glucose and glycerol by c14dm�mutants (Fig 6), a possible adaptive response to their high demand for carbon sources.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…While glycerol could be converted into glucose, it is unlikely to account for the rescue as the energy required for gluconeogenesis exceeds that generated from glycolysis. Instead, it is possible that Leishmania parasites metabolize glycerol into glycerol-3-phosphate (by glycerol kinase) and then dihydroxyacetone phosphate (by the mitochondrial FAD-dependent glycerol-3-phosphate dehydrogenase) which can be incorporated into the glycolysis pathway, as described in T. brucei [50,51]. We also observed increased uptake of glucose and glycerol by c14dm�mutants (Fig 6), a possible adaptive response to their high demand for carbon sources.…”
Section: Discussionmentioning
confidence: 54%
“…Recent studies have revealed that bloodstream forms of Trypanosoma brucei can use glycerol to support growth in the absence of glucose [50,51]. To test if Leishmania parasites can utilize glycerol effectively, we attempted to rescue c14dm�mutants with glycerol.…”
Section: Glucose Starvation Has Deleterious Effect On C14dm�parasitesmentioning
confidence: 99%
“…For the LC-MS metabolomic analysis, the sample extraction was performed as described previously [81,82]. Briefly, 5 × 10 7 cells were used for each sample.…”
Section: Lc-ms Metabolomic Analysismentioning
confidence: 99%
“…Nonetheless, a significant amount of cytosolic NADPH has been shown to be produced by the PPP (ca. 25% in bloodstream T. brucei ) due to gluconeogenesis fueled by glycerol (in the mammalian stage) [ 12 ] or proline (in the insect stage) [ 13 ]. G6PDH [ 14 ] and 6PGDH [ 15 ] proved indispensable for the bloodstream form of T. brucei , though it remains unclear whether this is a consequence of a shortage of NAPDH and/or ribose 5-phosphate.…”
Section: Introductionmentioning
confidence: 99%